Analysing the difficulty of constitutional reform in the Philippines - Yusingco, Michael Henry (Đại học Quốc Gia Hà Nội, 2020)
Initiatives to change a constitution is part and parcel of being a constitutional democracy. Resisting such an initiative, provided it is supported by a rational public deliberative process, is an integral component of constitutional democracy as well. As a constitutional democracy, the Philippines finds itself perfectly within this constitutional reform context. This paper analyzes the long history of charter change initiatives in the country and draws out the reasons why the 1987 Philippine Constitution continues to remain immune from reform and amendment. First, the way the amendment process is articulated in the text has given rise to contesting views making the launching of a strong and united initiative to amend or revise the charter very difficult. Second, the political context surrounding all the moves to amend or revise the 1987 Constitution has always been dominated by a lack of trust, specifically directed at those pushing for it. Indeed, a trust deficit so severe, proponents have always failed to garner national support for their cause. Third, there is a subtext in the evolution of the country’s constitutional order that underpins the endurance of the 1987 Constitution and that is the supremacy of its Supreme Court in determining what it means. Because of this, a culture of critical constitutional analysis in the community has never been cultivated. Consequently, a consensus of amending or revising the charter has never naturally evolved. A profound disconnect between citizens and the charter has made it impossible to launch a credible charter change initiative. But the moment calls for Filipinos to deeply reflect on their national charter and how this has impacted the political economy of the country for the past three decades. Therefore, understanding these reasons is imperative for the nation’s constitutional maturity and must be studied further as part of a constitutional reform project.